Global Warming and a Potential Tipping Point in the Atlantic Thermohaline Circulation: The Role of Risk Aversion - Nicole Glanemann; Mariia Belaia; Michael Funke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The risk of catastrophes is one of the greatest threats by climate change. Yet, the most common Integrated Assessment Models produce the counterintuitive result that a higher concern about climate change risks does not lead to stronger near-term abatement efforts. This paper probes whether this result still holds in a more refined DICE model that features Epstein-Zin utility, uncertainty about climate sensitivity and is fully coupled with a dynamic representation of the Atlantic thermohaline circulation. This modelling allows posing the question of whether aversion to this specific tipping point risk has a significant effect on the climate policy efforts. The simulations, however, show that near-term policy is insensitive to this climate change risk. For the more likely climate sensitivity values, a collapse of the circulation would occur in the more distant future, which allows acting after learning. For the more unlikely and higher climate sensitivity values, the collapse is not prevented as climate policy costs would be too high.
Keywords: Q54; C61; C63; 330